Momordica dioica: Phytochemistry, Traditional Uses and It's Neuroprotective Activity - Sarwade, Prakash Pralhad; Kumar S.R., Santosh; Sonwani, Kalpana; Geetha, M.; Gajendhini, S.; Shanmugapriya, S. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Momordica dioica Roxb. ex Willd. (being spiny gourd or teasel gourd) is a climber plant of Cucurbitaceae family, which is extensively found in tropical and subtropical parts of Asia. Historically, it has been used in different native healing of health conditions like diabetes, inflammation, liver disorder, gastrointestinal conditions and reproductive problems. The paper is going to examine the chemical composition of phytochemicals, ethnomedicinal significance and neuroprotective potential of M. dioica against the background of modern pharmacological literature. Phytochemical studies indicate that a wide variety of bioactive chemicals are contained in M. dioica, with traces of flavonoids (quercetin, kaempferol), phenolic acids (gallic acid, ferulic acid), triterpenoids (ursolic acid, oleanolic acid), saponins, alkaloids, glycosides, and essential micronutrients. These compounds add to the broad pharmacological actions of the plant that include antioxidant, anti-inflammatory, antidiabetic, antil-micros and hepatoprotecs. Especially notable among them is the neuroprotective effect of M. dioica, ascribable to its actions on reducing the impacts of oxidative stress, inhibiting neuroinflammation, regulating cholinergic transmission, and enhancing neuronal survival. Based on preclinical studies, M. dioica may alleviate neuronal injury, improve memory task-performance, and prevent neurodegeneration by a variety of molecular pathways. These results are consistent with old knowledge, but there is only a clinical confirmation of these, which is only limited, and such information requires additional research that needs to be conducted on bioassay-guided isolation, pharmacokinetics, and human tests. Finally, Momordica dioica is an encouraging medicinal herb that possesses multi-targeted pharmacological effects and has a beneficial impact as a future therapeutic agent in neurodegenerative processes. Concluding this review, in the modality of incorporating both traditional use and modern scientific validation of plant-based therapeutics to build an environment of safe, effective, and cost-effective drug development to the field of neuropharmacology and the entire science of biomedicine deserves consideration.